The association between health-related quality-of-life scores and clinical outcomes in metastatic castration-resistant prostate cancer patients: Exploratory analyses of AFFIRM and PREVAIL studies. (December 2017) - Beer, Tomasz M.; Miller, Kurt; Tombal, Bertrand; Cella, David; Phung, De; Holmstrom, Stefan; Ivanescu, Cristina; Skaltsa, Konstantina; Naidoo, Shevani
Abstract: Background: Our exploratory analysis examined the association between health-related quality of life (HRQoL) (baseline and change over time) and clinical outcomes (overall survival [OS]/radiographic progression-free survival [rPFS]) in metastatic castration-resistant prostate cancer (mCRPC). Methods: HRQoL, OS and rPFS were assessed in phase III trials comparing enzalutamide with placebo in chemotherapy-naïve (PREVAIL;NCT01212991 ) or post-chemotherapy (AFFIRM;NCT00974311 ) mCRPC. HRQoL was assessed using the Functional Assessment of Cancer Therapy-Prostate (FACT-P). Multivariate analyses evaluated the prognostic significance of baseline and time-dependent scores after adjusting for treatment and clinical/demographic variables. Hazard ratios (HRs) and 95% confidence intervals (CIs) represented the hazard of rPFS or OS per minimally important difference (MID) score change in HRQoL variables. Results: In baseline and time-dependent multivariate analyses, OS was independently associated with multiple HRQoL measures across both studies. In time-dependent analyses, a 10-point (upper bound of MID range) increase (improvement) in FACT-P total score was associated with reductions in mortality risk of 19% in AFFIRM (HR 0.81 [95% CI 0.78–0.84]) and 21% in PREVAIL (HR 0.79 [0.76–0.83]). For baseline analyses, a 10-point increase in FACT-P total score was associated with reductions in mortality risk of 12% (HR 0.88 [0.84–0.93]) and 10% (HR 0.90 [0.86–0.95]) in AFFIRM and PREVAIL, respectively. rPFS was associated with a subset of HRQoL domains in both studies. Conclusion: Several baseline HRQoL domains were prognostic for rPFS and OS in patients with mCRPC, and this association was maintained during treatment, indicating that changes in HRQoL are informative for patients' expected survival. Highlights: Data from metastatic castration-resistant prostate cancer (mCRPC) trials were used. Health-related quality of life (HRQoL) is an important end-point in cancer trials. HRQoL measures may be prognostic indicators of survival. In this study, several baseline HRQoL domains were prognostic for survival in mCRPC. Changes in HRQoL are informative for patients' expected survival.